Effectiveness and safety of same day discharge after left atrial appendage closure under moderate conscious sedation. Issue 5 (16th November 2020) - Marmagkiolis, Konstantinos; Ates, Ismail; Kose, Gulcan; Iliescu, Cezar; Cilingiroglu, Mehmet
Abstract: Background: Left atrial appendage occlusion (LAAO) using Watchman device has become a world‐wide, well‐established therapeutic alternative to chronic systemic oral anticoagulation in patient who are at high‐risk of bleeding with paroxysmal (PAF) or chronic atrial fibrillation (Afib). Currently, LAAO procedures are performed under general anesthesia (GA) and patients stay overnight post procedure in the United States. We aimed to present the effectiveness and safety of same day discharge following LAAO under moderate conscious sedation (MCS) in patients without procedural complications. Methods: A total of 112 patients between August 2019 and May 2020 with elevated CHA2 DS2 VASc (median score of 3) underwent transesophageal echocardiography (TEE)‐guided LAAO with FDA approved Watchman (Boston Scientific, MN) under MCS and discharged home on the same day 6 hr following their post procedural transthoracic echocardiogram (TTE) evaluations. All patients had next day TTE and follow up at the cardiology clinic. We prospectively evaluated clinical and procedural outcomes using medical records of these patients. Results: Among all the patients, the mean age was 83.5 ± 8.5 years, 45 (40%) were women. Procedural duration, device implant time and fluoroscopic times were 45 ± 8.6, 14.5 ± 7.8 and 10.2 ± 1.2 min, respectively. The median required dosage of propofol was 105 ± 2.8 mg. No complications arose from MCS. There was no need for conversion to GA in any of the patients during the procedure. All patients were able to be discharged 6 hr following their TTE evaluation post procedure. There were no procedural complications. Conclusions: Same day discharge following LAAO closure seems to be safe and effective in patients without procedural complications. LAAO can also be performed safely and effectively under moderate conscious sedation. Applying moderate conscious sedation may simplify the LAAO procedure, reduce procedural time, procedural costs and hospital stay while increasing overall patient satisfaction.